(untitled) (e-Journal of Linguistics, 2023)
This research aims to construct news headlines related to COVID-19 terms in Indonesia. The data source is from various online news media such as health.detiknews.com, kompas.com, and liputan6.com. Data was collected by only selecting headline news text with istilah (terms) and COVID-19. The data were analyzed using Norman Fairclough’s critical discourse analysis approach. The results showed that through the microstructural dimension, the eight news headlines used linguistic tools with 1) diction or vocabulary selection focused on the use of the word COVID-19, and 2) grammatical units dominated by phrases, 3) syntactic functions dominated by descriptions as topicalization of discourse, and 4) the form of news that is emphasized on statements regarding the change or replacement of various terms related to COVID-19. Then, through the mesostructural dimension, the three online mass media have different characteristics and characters in delivering news, especially related to COVID-19 terms, but still being presented accurately and objectively so that news content can be conveyed to readers. Finally, through the macrostructural dimension, it was revealed that a political system demonstrated the power of the government and the Ministry of Health in determining the use of various COVID-19 terms in Indonesia.